SUGGESTIONS FOR GLOBAL ISSUES IN LANGUAGE EDUCATION MATERIALS AND ACTIVITIES - Gregory Goodmacher; Asako Kajiura (Universitas Ahmad Dahlan)
Universities and other centers of learning are joining with the United Nations and other international institutions to further the study of significant issues that are affecting the lives of people across the globe. Ministries of education in various countries want to have their students develop an understanding of the concept of global citizenship and the connections between the peoples of our increasingly intertwined world. In line with this, many educational institutions are including global issues education in their curricula. The English language is the predominant language of international business, globalization, medicine, international education, and politics. Billions of people are studying and using English daily. Can language teachers play a part in promoting global citizenship and creating a peaceful and sustainable world? This paper aims to answer that question and to address vital principles involved in the creation of activities and teaching materials that merge global issues content and language education. It will also provide examples of how teachers can combine content education and critical thinking skills in ways that develop grammatical knowledge and the traditional skills of reading, writing, speaking, and listening.